Rasch Validation of the Arabic Version of the Behavioral Intention to Interact With Peers With Intellectual Disability Scale - Alnahdi, Ghaleb H. (Frontiers in Psychology, 2019)
This study aimed to examine the construct validity of the Arabic version of the behavioral intention to interact with peers using an intellectual disability scale. Rasch analysis was used to examine the psychometric properties of the scale. The sample contained 290 elementary students in Saudi Arabia (56% were girls and 44% were boys). Several parameters were examined: overall fit, item fit, person fit, assumption of local independency, and the scale’s unidimensionality. Eight items were rescored, 22 misfit persons were removed, and no item with differential item functioning was detected. Disordered thresholds were detected in eight items. The scale demonstrated good internal consistency (person separation index 0.80) and fulfilled all the requirements of the Rasch model. After rescoring the eight items, Rasch analysis supported the scale’s unidimensionality to measure children’s behavioral intention to interact with peers with intellectual disability. The Arabic version of the scale, with the proposed scoring, could be a useful tool to measure children’s behavioral intention to interact with peers with intellectual disability. Further studies with different samples are warranted to confirm the study’s findings.